Supervisi Akademik di SMP Negeri 4 Pacitan - Supratikto, Adi; Supriyanto, Eko; Fathoni, Ahmad (Universitas Muhammadiyah Surakarta, 2014)
Academic supervision is series activity assist teachers to develop their abilities to organize learning process for reach the goal. Headmaster must arrange academic supervision at school as wellas implementation of Permendiknas No. 13 Tahun 2007. The problem ist facton the field which shows many headmasters feel reluctant to do it. So,it was held research at SMP Negeri 4 Pacitan with the goal to gain illustrations: (1) characteristic of academic supervision preparation at SMPN 4 P Pacitan, (2) Characteristic of academic supervision implementation at SMPN 4, (3) characteristic of the advantageous academic supervision implementationat SMPN 4 Pacitan.The research method was used of is qualitatif research with etnografi study approach by naturalistic paradigm. The data source an resource person were administration document, teacher, and headmaster. The techniques of collecting data were observation, interview, and documentation. The data analysis was descriptife qualitatif with the data validity, Examination used triangulation technique.Based on the research, was gained descriptif results: (1) characteristic of academic supervision preparation, (2) characteristic of academic supervision was done when teacher was doing learning proces in calss, (3) characteristic of advantageousacademic supervision implementation at SMPN 4 between: increasingteacher and headmaster competence, so the would more professional and increasing students achievement.